Simulasi Tanggap Bencana Melalui Sosialisai Kebencanaan Dan Pengenalan Ilmu Kebumian Di SMP Negeri 19 Kota Palu - Arum, Deno Ambar; Saputra, Apriadi; Permatasyara M, Risqa; Uno, Djamal Adi Nugroho (-, 2025)
Indonesia is highly vulnerable to geological disasters, especially earthquakes and secondary hazards, due to its location at tectonic plate boundaries and active faults. However, junior high school students’ understanding of earth science and disaster mitigation remains low. This community service project aimed to enhance disaster literacy through interactive socialization at SMP Negeri 19 Palu (high-risk earthquake area). Methods included lectures, group discussions, educational videos, and disaster response simulations, focusing on earth science fundamentals (earth structure, rocks, geological processes) and mitigation measures for earthquakes, tsunamis, and liquefaction. Participants were Grade VIII students, selected for their potential as agents of change. Results demonstrated increased disaster awareness, mitigation knowledge, and interest in earth science. The activity fostered early disaster preparedness culture and established university-school partnerships, supporting education-based disaster risk reduction programs. Positive feedback from students and the school confirmed the effectiveness of the communicative approach.